Preconception Health of Prospective Brides and Grooms in Malang Regency, Indonesia - Tazkiyah, Nadya Dina; Suprapti, Suprapti; Wulandari, Lisa Purbawaning; Sunaeni, Sunaeni; Mansur, Herawati (Al-Sihah : The Public Health Science Journal, 2024)
Preconception health is a significant contributor to pregnancy outcomes. However, the majority of women only improve their health status after receiving counseling at the first antenatal visit or during pregnancy. This shows the need to identify preconception health through premarital screening. Therefore, this study aimed to assess the characteristics of preconception health of prospective brides in Malang Regency using "Elsimil Application". The assessment was carried out using a quantitative descriptive method with a secondary data analysis. The total sampling method was used for sample collection and data used were obtained from prospective brides who completed the premarital screening questionnaire on Elsimil Application. The variables assessed were prospective brides’ preconception health with several sub-variables. These included age, BMI, Hb levels, upper arm circumference, and smoking behavior, which were collected using an instrument in the form of a checklist table. The results of the descriptive statistical analysis, which included the frequency and percentage, showed that a significant proportion of prospective brides had preconception health state at risk (61.1%). Consequently, this study recommended the importance of strengthening preconception health services by providing education, which comprised accurate information, accessibility, and required improvement, particularly for prospective brides and grooms in rural areas.